Endocardium modulates myocardial contractile performance in isolated guinea pig papillary muscles - Chu Guo-Xiang; Guo Zhao-Gui (Acta Pharmacologica Sinica, 2016)
Selective removal of endocardium by 1-s immersion of the muscle into 0.5% Triton X-100 resulted in a significant reduction of PT (peak isometric twitch tension) at 1.25 mmol.L-1 [Ca2+]o over the stimulation frequency from 0.2 to 2.0 Hz (3.2 +/- 0.2 vs 4.4 +/- 0.4 mN/mm2 at 1 Hz, P < 0.01), while +dT/dtmax was unaltered. Tension-[Ca2+]o relation was shifted in accordance to [Ca2+]o, but with no significant change on PT at high [Ca2+]o compared with endocardium-intact muscles. TPT (time to peak isometric tension) and RT1/2 (half isometric relaxation time) were typically shortened at all [Ca2+]o or various stimulation frequencies (TPT: 203 +/- 18 vs 265 +/- 37 ms; RT1/2: 77 +/- 10 vs 108 +/- 26 ms, at 1.25 mmol.L-1 and 1 Hz, P < 0.01). Stimulation duration-threshold curve was slightly shifted to the left, yet no change in ERP (effective refractory period) was found. The data demonstrated that endocardium was an important modulator of myocardial contractile performance.